1994
DOI: 10.1128/aem.60.7.2304-2310.1994
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the crystal protein gene under the control of the alpha-amylase promoter in Bacillus thuringiensis strains

Abstract: The expression of an insecticidal crystal protein gene of Bacillus thuringiensis under the control of the a-amylase gene promoter was investigated. The crylC gene, which encodes a protein known to have a unique activity against Spodoptera (armyworm) species, was used in this investigation. The cryIC gene was placed, along with the a-amylase promoter from B. subtilis, in a B. thuringiensis-derived cloning vector, generating a pair of recombinant plasmids, pSB744 and pSB745. The cloning vector that contains the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The average Bt index recorded in the study was 0.62, which means that 62% of the sporulating colonies examined showed the presence of crystals. The average is higher compared to some previous isolation programs (less than 0.1 to 0.52) (Bravo et al., ; Chak, Tsen, & Yamamoto, ; Vidal‐Quist, Castañera, & González‐Cabrera, ), lower compared to that observed (0.85) by Martin and Travers () and similar to that observed (0.6 to 0.7) by Obeidat, Hassawi, and Ghabeish (). Lake sediments showed the least Bt index (0.25), whereas forest soils showed the highest Bt index (0.76) (Table ).…”
Section: Discussionsupporting
confidence: 56%
“…The average Bt index recorded in the study was 0.62, which means that 62% of the sporulating colonies examined showed the presence of crystals. The average is higher compared to some previous isolation programs (less than 0.1 to 0.52) (Bravo et al., ; Chak, Tsen, & Yamamoto, ; Vidal‐Quist, Castañera, & González‐Cabrera, ), lower compared to that observed (0.85) by Martin and Travers () and similar to that observed (0.6 to 0.7) by Obeidat, Hassawi, and Ghabeish (). Lake sediments showed the least Bt index (0.25), whereas forest soils showed the highest Bt index (0.76) (Table ).…”
Section: Discussionsupporting
confidence: 56%
“…A variety of shuttle vectors, some employing B. thuringiensis plasmid replicons (17,28,63,122), has been used to introduce cloned cry genes into B. thuringiensis (124). Alternatively, integrational vectors have been used to insert cry genes by homologous recombination into resident plasmids (2,219) or the chromosome (176).…”
Section: Developing New Cry Biopesticides Basedmentioning
confidence: 99%
“…It has been shown that C-terminally truncated versions of different Cry proteins and even 5Ј translational fusions with nptII are capable of exerting the insecticidal effect as long as the specific trypsin cleavage sites which delimit the toxin are maintained (16,32,46,48). The strict specificity of the receptor-toxin interaction has promoted the use of cry genes as very promising tools to construct insecticidal bacteria and transgenic plants with specific insect resistance (6,12,25,28). While in cry-carrying bacteria and plant chloroplasts (25) high levels of Cry proteins have been recorded, the native cry genes were poorly expressed as plant nuclear transgenes, and consequently their larvicidal activity was limited (12).…”
mentioning
confidence: 99%